Determinants of primaquine and carboxyprimaquine exposures in children and adults with Plasmodium vivax malaria - Chu, CS; Watson, JA; Phyo, AP; Win, HH; Yotyingaphiram, W; Thinraow, S; Soe, NL; Aung, AA; Wilaisrisak, P; Kraft, K; Imwong, M; Hanpithakpong, W; et al. (American Society for Microbiology, 2021)
Background Primaquine is the only widely available drug for radical cure of Plasmodium vivax malaria. There is uncertainty whether the pharmacokinetic properties of primaquine are altered significantly in childhood or not. Methods Glucose-6-phosphate dehydrogenase normal patients with uncomplicated P. vivax malaria were randomized to receive either chloroquine (25mg base/kg) or dihydroartemisinin-piperaquine (dihydroartemisinin 7mg/kg and piperaquine 55mg/kg) plus primaquine; given either as 0.5 mg base/kg/day for 14 days or 1 mg/kg/day for 7 days. Pre-dose day 7 venous plasma concentrations of chloroquine, desethylchloroquine, piperaquine, primaquine and carboxyprimaquine were measured. Methemoglobin levels were measured on day 7. Results Day 7 primaquine and carboxyprimaquine concentrations were available for 641 patients. After adjustment for the primaquine mg/kg daily dose, day of sampling, partner drug, and fever clearance, there was a significant non-linear relationship between age and trough primaquine and carboxyprimaquine concentrations, and day methemoglobin levels. Compared to adults 30 years of age, children 5 years of age had trough primaquine concentrations 0.53 (95% CI: 0.39- 0.73) fold lower, trough carboxyprimaquine concentrations 0.45 (95% CI: 0.35- 0.55) fold lower, and day 7 methemoglobin levels 0.87 (95% CI: 0.58-1.27) fold lower. Increasing concentrations of piperaquine and chloroquine and poor metabolizer CYP 2D6 alleles were associated with higher day 7 primaquine and carboxyprimaquine concentrations. Higher blood methemoglobin concentrations were associated with a lower risk of recurrence. Conclusion Young children have lower primaquine and carboxyprimaquine exposures, and lower levels of methemoglobinemia, than adults. Young children may need higher weight adjusted primaquine doses than adults.